Strategies for preventing and controlling overweight and obesity among high school students in Kiribati - Tong, Tanebu Julia; Mohammadnezhad, Masoud; Alqahtani, Nasser Salem (Frontiers in Nutrition, 2025)
IntroductionOverweight and obesity are rising concerns particularly in Pacific Island Countries (PICs) where healthcare capacity is limited. However, limited studies have explored school-based prevention strategies in Kiribati. This study aims to identify effective strategies for preventing and controlling overweight and obesity among senior high school students in Kiribati, including curriculum and policy changes, nutrition education, and exercise interventions.MethodsThis mixed-methods study employed a prospective observational approach across four randomly selected senior high schools in South Tarawa, Kiribati from August to November 2020. Purposive sampling was used to select study participants. A total of 32 students (aged 13–19) and 20 School Committee Members (SCMs) participated in semi-structured interviews and Focus Group Discussions (FGDs). Qualitative Data were collected using the International Physical Activity Questionnaire (IPAQ) and Food Frequency Questionnaire (FFQ). Descriptive statistics, chi-square tests, and logistic regression analysis were conducted to determine associations between student behaviors and overweight/obesity prevalence. Measures were taken to reduce selection bias, including stratified sampling based on school size and student demographics.ResultsNone of the schools had physical education or nutritional health courses in their curriculum. Unhealthy dietary patterns, insufficient physical activity, and substance use (kava, alcohol, and tobacco) were prevalent among students. Statistical analysis revealed significant differences in overweight and obesity prevalence among the four schools (p = 0.04), with students from central and western schools exhibiting higher obesity rates. Meal skipping (OR = 2.4, 95% CI: 1.21–4.97, p0.03) and low sports involvement (OR = 3.12, 95% CI: 1.45–6.73, p = 0.01) were significantly associated with overweight and obesity. SCMs reported policy gaps and lack of implementation regarding student health and nutrition.ConclusionThe absence of structured physical education, inadequate health policies, and poor implementation contribute to overweight and obesity among high school students in Kiribati. Policy revisions, curriculum integration of health education, and school-based intervention programs are necessary to address these issues. Furthermore, regional differences in school environments should be considered when designing interventions.